Properties of concrete having treated recycled coarse aggregate and slag - Saravanakumar, P.; Manoj , D.; Jagan , S. (Revista de la Construcción. Journal of Construction, 2021)
<span style="font-size: 10.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Calibri’,sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The possibility of using substitute materials for aggregates and cement in concrete were studied and reported in this paper. Concrete mixtures with untreated recycled coarse aggregates (URCA) and treated recycled coarse aggregates (TRCA) were used to prepare two mix groups of without slag (Mix I) and with slag (Mix II). The recycled aggregates were treated with hydrochloric acid (HCl) having different molarities (0.1M, 0.3M and 0.5M) before used as a substitute material for virgin aggregate in concrete. The concrete mechanical, durability properties and morphology of concrete were examined through standard experiments and analysed. In both mix groups considerable improvement in all characteristics were identified in TRCA mixes than URCA mixes. Among the two mix groups the concrete mix with slag (Mix II) showed better durability characteristics than mix without slag (Mix I). The combination of TRCA and slag in concrete substantially increases the characteristics of concrete in all means.